The Use of Politeness Strategy on Comment in Politicians Twitter - Aminatus Sholehah; Etika Dewi Kusumaningtyas (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
This research in title “The use of politenes strategy on comment in politician twitter account". The problems of this research are: What kinds of Politeness Strategies used by the netizens comment in politician twitter account & What are the functions of Politeness Strategies used by the netizens comment in politician twitter account. The researcher used descriptive qualitative method. The purpose of this research is to identify, classify, analyze the function and types of politeness strategies in used that can be shown in the conversation in the twitter comment . In collecting data, the writer concentrates the utterance‟s which contains the politeness strategies produced by the netizens comment in politician twitter account . The result of the research, there are 4 strategies that are used by the netizens bald-on record, positive politeness, negative politeness, and off record.